ANALISIS PEMBINAAN KARAKTER BERDASARKAN UU NO 35 TAHUN 2009 BAGI NARAPIDANA NARKOTIKA DI LEMBAGA PEMASYARAKATAN KELAS II A KOTA JAMBI - Pratiwi, Cahyani Sekar; Maulia, Siti Tiara; Ekawarna, Ekawarna (Academy of Education Journal, 2023)
This research aims to determine character development for prisoners when viewed based on Law No. 35 of 2009 in class II A correctional institutions in Jambi City, and to determine the inhibiting factors in character development for prisoners and efforts to overcome these obstacles. The research approach used in this research is a qualitative approach. This type of research is a type of descriptive research where the author describes, describes an ongoing situation based on information and facts that have been obtained in the field and then analyzed based on one variable to another. The results of the research show that character development for prisoners in class II A correctional institutions in Jambi City when viewed from Law no. 35 of 2009 article 60 paragraphs 1 and 2 concerning guidance and supervision, most of its implementation has been carried out well. Penitentiary is a place of social rehabilitation for prisoners. Prisons have established development programs. Coaching consists of developing personality and independence. Both types of coaching have the same goal, namely providing teaching so that prisoners or inmates become better than before. The inhibiting factors for ongoing character development for narcotics convicts are firstly overcapacity, secondly a lack of officers, and thirdly a lack of focus among prisoners during the coaching process.